Commodity fundamentals : - Spurga, Ronald C. (John Wiley & Sons, 2006)
Commodity Fundamentals provides you with the in-depth insights needed to make commodities trading a profitable, integral component of your overall trading activities. Written by Ronald Spurga, a Vice President of ABN AMRO Bank and longtime veteran of the investment banking wars, this straightforward guide arms you with the information you need to succeed in the highly profitable commodity marketplace-whether you are a trading veteran, a relative newcomer, or anywhere in between.